Perancangan Sistem Informasi Kedai Kopi Menggunakan Metode Rapid Application Development (RAD) - Ardhana, Valian Yoga Pudya (Yayasan Pendidikan Penelitian Pengabdian Algero, 2024)
The development and speed of information technology in the industrial revolution 4.0 requires companies or business people to switch to using systems that are able to work together and collaborate between technology and human resources. Current technological developments also have an impact on MSME business actors, especially culinary. For example, coffee shop, usually in the ordering process, coffee shops still use a manual ordering process. In this process, customers who come in must enter, order and immediately pay manually. This is of course risky for the company because the data could be lost or damaged. This problem occurs because there is no system that can support the ordering process, manage incoming data, market and introduce the product to reach the wider community. Customers sometimes find it difficult to get the latest updated information regarding available menus and the ordering and payment process. For this reason, an information system is needed so that problems can be resolved. With the Rapid Application Development (RAD) approach, the coffee shop information system can be developed relatively quickly and produce a system that suits your needs. This web-based coffee shop information system has the features that coffee shop entrepreneurs need to run their business effectively and efficiently and makes ordering and payment easier for customers. Apart from that, the test results using black-box testing produced a score of 100%, this means that the features contained in the system are in accordance with requirements.